2010
DOI: 10.1111/j.1365-2826.2010.02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Endocannabinoid System‐Mediated Actions of Rimonabant on Growth Hormone Secretion are Ghrelin‐Dependent

Abstract: The somatotroph axis is a crucial pathway regulating metabolism. Despite the fact that the endocannabinoid system has been also revealed as a potent modulator of energy homeostasis, little information is available concerning a putative interaction between these two systems. The aim of the present study was to determine the in vivo effects of the blockade of the cannabinoid receptor type 1 (CB1) over growth hormone (GH) secretion using the CB1 antagonist rimonabant. The results obtained show that the blockade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Some evidences for a peripheral influence of CB1 receptors on ghrelin actions have also been documented, giving some insight into our results. First of all, blockade of peripheral CB1 receptors decreases central actions of ghrelin such as ghrelin-induced growth hormone secretion, by a CB1 receptor mediated inhibition of hypothalamic GHRH mRNA expression that requires intact vagal afferent fibers [48]. Secondly, SR141716A reduce circulating plasma ghrelin levels in fed rats suggesting a modulatory control of peripheral CB1 receptors on ghrelin secretion by the gastrointestinal tract [49].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidences for a peripheral influence of CB1 receptors on ghrelin actions have also been documented, giving some insight into our results. First of all, blockade of peripheral CB1 receptors decreases central actions of ghrelin such as ghrelin-induced growth hormone secretion, by a CB1 receptor mediated inhibition of hypothalamic GHRH mRNA expression that requires intact vagal afferent fibers [48]. Secondly, SR141716A reduce circulating plasma ghrelin levels in fed rats suggesting a modulatory control of peripheral CB1 receptors on ghrelin secretion by the gastrointestinal tract [49].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed assays on pulsatile GH release and GH receptor signal transduction in Cnr1 KO mice might allow a further delineation of the role of Cnr1 in the control of the GH/IGF-I axis and growth (and possibly glucose metabolism), although the small plasma volume of mice makes frequent sampling impractical. Nonetheless, it is worth pointing out that one study has shown that pharmacologic blockade of peripheral Cnr1 signaling inhibited pituitary GH pulsatile secretion (19). Consistent with this, we observed a reduction in plasma GH levels in 6-week-old Cnr1 KO mice, although this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the present findings, it is reasonable to hypothesize that 2-AG and anandamide act by engaging CB 1 receptors, which are present on enteric neurons and vagal fibers (20), thus modifying the generation or action of neurohumoral factors that affect satiation (meal size) and satiety (intermeal interval), such as ghrelin (25). Although the identification of these factors must await future experimentation, our study does suggest that pharmacological strategies aimed at curbing endocannabinoid activity in the gut might selectively lower the intake of fat-rich foods, a major drive behind overweight and obesity, without affecting reward systems in the brain.…”
Section: Discussionmentioning
confidence: 99%